Engaging Child Welfare–Involved Families in Evidence-Based Interventions to Address Child Disruptive Behavior Disorders. (March 2020) - Lewis, Ericka M.; Hooley, Cole; Feely, Megan; Lanier, Paul; Korff, Suzanne J.; Kohl, Patricia L.
Evidence-based behavioral parent training (BPT) programs are the most effective way to address children's behavior disorders and participant engagement is essential to achieving positive treatment outcomes. However, there is limited understanding of the factors that contribute to engagement, particularly for at-risk families. This qualitative study explored factors affecting behavioral and attitudinal engagement among child welfare–involved parents participating in Pathways Triple P ( n = 47). Data were collected through semistructured interviews and three major themes affecting parental engagement were identified: (a) ensuring comprehension, (b) increasing parenting efficacy, and (c) addressing obstacles to participation. Findings suggest that practitioner behaviors play an essential role in increasing the engagement of families receiving BPT, and identify practitioners as a promising strategy to improve program effectiveness for parents involved with child welfare.